Objective Resident Characteristics Associated with Performance on the Ophthalmic Knowledge Assessment Program Examination - Fliotsos, Michael J.; Zafar, Sidra; Dharssi, Shazia; Srikumaran, Divya; Chow, Jessica; Singman, Eric L.; Woreta, Fasika A. (Journal of Academic Ophthalmology, 2021)
Background To determine objective resident characteristics that correlate with Ophthalmic Knowledge Assessment Program (OKAP) performance, as well as to correlate OKAP performance with Accreditation Council for Graduate Medical Education (ACGME) milestone assessments, written qualifying examination (WQE) scores, and oral board pass rates.Methods Review of administrative records at an ACGME-accredited ophthalmology residency training program at an urban, tertiary academic medical center.Results The study included data from a total of 50 resident physicians who completed training from 2012 to 2018. Mean (standard deviation) OKAP percentile performance was 60.90 (27.51), 60.46 (28.12), and 60.55 (27.43) for Years 1, 2, and 3 examinations, respectively. There were no statistically significant differences based on sex, marital status, having children, MD/PhD degree, other additional degree, number of publications, number of first author publications, or grades on medical school medicine and surgery rotations. OKAP percentile scores were significantly associated with United States Medical Licensing Examination (USMLE) Step 1 scores (linear regression coefficient 0.88 [0.54–1.18], p = 0.008). Finally, continuous OKAP scores were significantly correlated with WQE (rs = 0.292, p = 0.049) and oral board (rs = 0.49, p = 0.001) scores.Conclusion Higher OKAP performance is correlated with passage of both WQE and oral board examinations during the first attempt. USMLE Step 1 score is the preresidency academic factor with the strongest association with success on the OKAP examination. Programs can utilize this information to identify those who may benefit from additional OKAP, WQE, and oral board preparation assistance.
Keywords: OKAP; Ophthalmic Knowledge Assessment Program; oral board examination; Accreditation Council for Graduate Medical Education; ACGME; ACGME milestones; ophthalmology residency; graduate medical education; United States Medical Licensing Examination; USMLE; ABO-WQE; written qualifying examination